Evaluation of new technique of mesh fixation in laparoscopic inguinal hernia repair - El Deep, Ahmed; Zeineldein, Ashraf A.; Soltan, Tamer A.; Fawzy, Ahmed N. (International Surgery Journal, 2020)
Background: Hernia is a common problem of the modern world with an incidence ranging from 5 to 7%. Of all groin hernias, around 75% are inguinal hernias. Recently with the advancement in laparoscopy, endoscopic repairs seem to offer better quality of life, decreasing hospital stay and early return to work. Aim of the work was to evaluate a new technique for mesh fixation by Zein method of suturing and compare it with stapled mesh fixation in laparoscopic inguinal hernia repair transabdominal preperitoneal approach. Methods: The study is a randomized, prospective single group study. The study was conducted after the approval of the ethical committee of the surgical department, Menoufia University. It was conducted in Menoufia University Hospital on 50 patients with inguinal hernia who were operated upon between September 2018 and September 2019 with a minimal follow-up of 6 months. Results: Age of studied patients ranged from 27 to 55 years with mean 42.82±7.90 age/years. Regarding sex of studied patients, more than half (74%) of studied patients were males and (26%) were females. Regarding comparsion between high and low overall cost burden on the patient, it was interestingly found that high cost is associated with presence of complication like hematoma, prolonged stay in the hospital and prolonged use of antibiotics. Conclusions: Both the use of sutures and fixation of mesh by absorbable tacks approaches are similarly effective in terms of operative time, the incidence of recurrence, complications, and chronic pain coinciding with all the available literature.